Penggunaan Carbormer 940 sebagai Gelling Agent dalam Formula Pasta Gigi Ekstrak Buah Apel (Malus sylvestris Mill) dalam Bentuk Gel - Wijayanti, Luh Putu Widiasih; Darsono, Farida Lanawati; Ervina, Martha (Jurnal Farmasi Sains dan Terapan, 2017)
Teeth are often not protected from several diseases, despite having a hard structure. Dental diseases include dental caries (cavities) and diseases of the tooth supporting tissues. Dental caries is defined as a disease that results in damage to the hard tissue of the tooth structure through the process of demineralization. Streptococcus mutans is known as a major microorganism that plays a role in the process of dental caries. One way to reduce the formation of dental caries is to use toothpaste. Apples (Malus sylvestris Mill) Manalagi variety that has catechins, has efficacy as an anti dental caries. The purpose of this study was to formulate ethanol extract from apples as a gel toothpaste using carbomer 940 as a gelling agent. Apple ethanol extract used in this study was 9.6%, while the carbomer concentration of 940 used was 0.75% (formula I), 1.0% (formula II) and 1.5% (formula III). Evaluation of toothpaste formulas includes physical quality including organoleptic, homogeneity, pH, viscosity, dispersibility. Characteristic evaluation includes ease of release from the tube, adhesion and consistency. The stability evaluation includes room temperature stability, high temperature, and cycling tests. Evaluation of aseptability and evaluation of irritation is done in cow's jaws. Increasing the concentration of Carbomer 940 as a gelling agent has a significant effect on viscosity, dispersion, ease of release from the tube, adhesion and consistency. The test results show formula 3 (1.5% carbomer 940) is the best formula because it has produced physical quality in accordance with specifications, the resulting preparation is stable and very preferred and safe to use.